EIF VC Survey 2018: Fund managers' market sentiment and views on public intervention - Helmut Kraemer-Eis; Antonia Botsari; Salome Gvetadze; Frank Lang (European Investment Fund (EIF), 2018)
This working paper presents results of the first EIF VC Survey, a survey among venture capital general partner/management companies. The study provides a detailed overview of the respondents' state of business and market activity as well as their general perception of the European venture capital market, including public intervention. In doing so, the study looks at the current situation, developments in the recent past, and expectations for the future.
Keywords: 330